A web-based system to reduce the nosocomial infection impact in healtcare units - Rigor, Hugo (2008)
The nosocomial infection has a critical impact on the mortality and morbidity of the patients in healthcare units, especially in intensive care units, and has been studied in order to be mitigated. The registration of information about this phenomenon in databases is, more and more, a reality, turning viable the representation of this information through mathematical formalisms that, conjugated with the application of Artificial Intelligence techniques, will allow the discovery of knowledge related with the critical factors, processes and infectious agents. The ultimate goal has been to construct a web-based computational tool to automate the registration process to support the clinical body work, monitoring the performance and identifying the procedures that can be implemented in order to reduce the impact of the infections.